Simulation of stationary, non-normal random process - Nguyen Cao Menh; Tran Duong Tri (Vietnam Journal of Mechanics)
Simulation of stationary random processes specified by spectral density function and NonNormal probability density function has been rarely studied, though these processes are often met in both theory and practice.